2017
DOI: 10.9734/jamb/2017/36529
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Bacterial Contaminants in Fin-fishes (Clarias gariepinus and Coptodon guineensis) from Humic Freshwater Ecosystem of Eniong River, Itu, Akwa Ibom State, Nigeria

Abstract: The occurrence of bacterial isolates in fin-fishes (Clarias gariepinus and Coptodon guineensis) from the humic ecosystem of Eniong River, Akwa Ibom State was investigated. The results obtained from pour plate analysis showed that the fin-fishes contained bacterial contaminants. The bacterial loads varied with the type of fin-fish and were much higher in fish intestines, when compared with the skin and gills. The heterotrophic bacterial loads obtained exceeded the 1.2 x 10 5 cfu/g limit recommended for fresh fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…This explains why the viable counts of different types of bacteria in the digestive tract varied with fish species. The high bacterial contaminants recorded for the fin-fishes was expected and is in agreement with previous report by Ajayi, [41] and Umana et al [42], who in his study reported a high bacterial population in catfish from fish pond and river respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This explains why the viable counts of different types of bacteria in the digestive tract varied with fish species. The high bacterial contaminants recorded for the fin-fishes was expected and is in agreement with previous report by Ajayi, [41] and Umana et al [42], who in his study reported a high bacterial population in catfish from fish pond and river respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Another bacterium of public health importance is Salmonella specie, the causative agent of salmonellosis, a disease that is characterized by enteric (or typhoid) fever along with gastroenteritis, abdominal cramps and diarrhoea (22). The predominance of Salmonella in crab in this study is associated with human and animal actions in the beach being an enteric bacterium from flora of both humans and animals (23,24). Staphylococcus aureus, Shigella and Salmonella are pathogens carried by human, and their occurrence in the crab and dog whelk shellfishes can be attributed to improper handling and cross contamination by humans.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, bacterial isolates were identified based on their cultural, morphological and biochemical characteristics according to Bergey's Manual of Determinative Bacteriology [8,9]. Biochemical characteristics were determined using a conventional biochemical test such as catalase, coagulase, indole, and citrate tests [10].…”
Section: Morphological and Biochemical Identification Of Isolatesmentioning
confidence: 99%